The Connotation and Realization of the Chinese Educationalist Spirit - LI Cong; CHEN Shijian (Jiaoshi jiaoyu xuebao)
The Chinese educationalist spirit embodies the integration of national spirit and the spirit of the times, serving as the driving force for teachers' professional development. Teachers in the new era should be guided by General Secretary Xi Jinping's important exposition on the spirit of educationalists. They should foster patriotism and loyalty to the Party, uphold integrity, boost teaching skills, innovate professionally, understand their inner selves, and lead educational innovation. The Chinese educationalist spirit not only enriches teachers' spiritual core and improves their professional quality but also facilitates the convergence of value consensus, thus bolstering the building of a strong educational nation. To promote and practice the Chinese educationalist spirits, three key approaches should be prioritized. Firstly, we should enhance teachers' rational consciousness to activate their intrinsic motivation for cultivating talents for the Party and the nation. Secondly, it is necessary to optimize institutional governance structures to construct positive educational ecosystems. Thirdly, we need to craft compelling narratives of eminent educationalists to foster a societal ethos that venerates teachers and prioritizes education.